2021
DOI: 10.1016/j.phymed.2020.153297
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options of TCM for organ injuries associated with COVID-19 and the underlying mechanism

Abstract: Background Coronavirus disease-2019 (COVID-19) caused by infection with severe acute respiratory coronavirus-2 (SARS-CoV-2) has been spreading rapidly throughout China and in other countries since the end of 2019. The World Health Organization (WHO) has declared that the epidemic is a public health emergency of international concerns. The timely and appropriate measures for treating COVID-19 in China, which are inseparable from the contribution of traditional Chinese medicine (TCM), have won much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…4 E), ( Zhang et al, 2020e ). SA exerts an important role in the neuroprotection of traumatic brain injury ( via the nuclear factor erythroid 2-related factor 2/antioxidant-response element pathway) ( Zhang et al, 2020d ), protecting the liver ( via decreasing aspartate aminotransferase and alanine aminotransferase activities) ( Peng et al, 2016 ), promoting cardiopulmonary resuscitation ( via increasing the expression of hypoxia-inducible factor-1α in the cerebral cortex) ( Du et al, 2011 ), and protecting acute lung injury ( via increasing myeloperoxidase activity and nitric oxide level in the lung ( Tian et al, 2011 ), and decreasing malondialdehyde and matrix metalloproteinase gelatinase B levels ( Du et al, 2012 )). Importantly, no observable cytotoxicity or adverse events both in vivo and in vitro with SA treatment have been reported to date.…”
Section: Promising Chinese Herbal Medicine Monomer Preparations For Tmentioning
confidence: 99%
See 1 more Smart Citation
“…4 E), ( Zhang et al, 2020e ). SA exerts an important role in the neuroprotection of traumatic brain injury ( via the nuclear factor erythroid 2-related factor 2/antioxidant-response element pathway) ( Zhang et al, 2020d ), protecting the liver ( via decreasing aspartate aminotransferase and alanine aminotransferase activities) ( Peng et al, 2016 ), promoting cardiopulmonary resuscitation ( via increasing the expression of hypoxia-inducible factor-1α in the cerebral cortex) ( Du et al, 2011 ), and protecting acute lung injury ( via increasing myeloperoxidase activity and nitric oxide level in the lung ( Tian et al, 2011 ), and decreasing malondialdehyde and matrix metalloproteinase gelatinase B levels ( Du et al, 2012 )). Importantly, no observable cytotoxicity or adverse events both in vivo and in vitro with SA treatment have been reported to date.…”
Section: Promising Chinese Herbal Medicine Monomer Preparations For Tmentioning
confidence: 99%
“…To better understand the activity of Chinese herbal medicine, more validation studies, with high-quality evidence (both in vitro and in vivo ), are now needed to systematically explore the underlying mechanisms. Furthermore, there is currently very little direct data associated with the protective effect of Chinese herbal medicines against extrapulmonary organ injuries during SARS-CoV-2 infection ( Zhang et al, 2020d ; He et al, 2020 ; Zhao et al, 2020 ). Nonetheless, Chinese herbal medicine has its own advantages.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“… Shang et al (2011) reviewed in detail the antiviral, antibacterial and antioxidative activities of Lonicera japonica as well as the isolation and characterization of more than 140 of its chemical constituents . Since then many further compounds were isolated from Lonicera japonica and characterized with respect to their pharmacological activities such as antiviral activities ( Yu et al, 2008 ; Ding et al, 2017 ; Li et al, 2018 ; Ge et al, 2019 ), suppression of inflammation-stimulating signaling pathways ( Kang et al, 2010 ; Kao et al, 2015 ; Kwon et al, 2015 ; Lee et al, 2015 ; Han et al, 2016 ; Zhang et al, 2020 ) or terminal enzymes ( Xu et al, 2007 ). As already stated in the Introduction, Lonicera japonica is one of the herbal medicines which were successfully used for the therapy of the SARS-CoV infected patients in the 2002/2003 SARS epidemic ( Liu et al, 2006 ; 2012a , 2012b ; Wang et al, 2014 ; Luo et al, 2020 ).…”
Section: Lonicera Japonica (Flos Lonicerae Japonicae)mentioning
confidence: 99%
“…While specific reviews on the toxic effects are rare or even absent as of yet, a tremendous number of investigations on antivirally active Chinese plants to inhibit SARS-CoV-2 and to cure COVID-19 have been published in the year 2020 (Huang et al, 2020 ; Luo et al, 2020 ; Li et al, 2020 ; Yang et al, 2020 ). Therefore, in the present review we focused only on toxicology and refer the reader to the excellent reviews on the pharmacology of anti-COVID-19 Chinese plants and clinical trials performed with Chinese herbal medicine to treat this pandemic that appeared in parallel in this special issue of Phytomedicine ( Hu et al, 2020 ; Wang et al, 2020 ; Xia et al, 2020 ; Zhang et al, 2020 ; Zhao et al, 2020 a; Zhao et al, 2020b ; Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As is known to all, COVID-19 has been well controlled in China, mainly due to the joint efforts of Chinese and western medicine, especially Chinese medicine, which has made outstanding contributions to improving patients’ symptoms and promoting recovery. [ 15 18 ] Acupuncture, as one of the traditional Chinese medicine treatment, has the advantage of quick effect, simple operation, and less pain, etc. Studies have shown that it can improve symptoms of dyspnea, relieve anxiety, treat insomnia, vomiting, and diarrhea, etc.…”
Section: Introductionmentioning
confidence: 99%